1964
DOI: 10.1128/jb.88.4.1056-1064.1964
|View full text |Cite
|
Sign up to set email alerts
|

Biohydrogenation of Unsaturated Fatty Acids by Rumen Bacteria

Abstract: A simple, rapid, specific assay for the biohydrogenation of unsaturated fatty acids was developed. With this assay, it was shown that washed suspensions of mixed rumen bacteria hydrogenate linoleic and oleic acids. Butyrivibrio fibrisolvens, a common rumen bacterium, is capable of hydrogenating linoleic acid to octadecenoic acid but not to stearic acid. Complete anaerobiosis is required, and with mixed rumen bacteria more activity is obtained in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0
5

Year Published

1967
1967
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 4 publications
8
83
0
5
Order By: Relevance
“…This response indicated that complete hydrogenation of 18:2n-6 to 18:0 decreased as 18:2n-6 input into the rumen increased. The net effect was accumulation of trans-18:1 isomers primarily (Table 3) as shown in vitro by Polan et al (1964). Feeding oils increased hydrogenation of 18:3n-3 compared with the control.…”
Section: Resultsmentioning
confidence: 91%
“…This response indicated that complete hydrogenation of 18:2n-6 to 18:0 decreased as 18:2n-6 input into the rumen increased. The net effect was accumulation of trans-18:1 isomers primarily (Table 3) as shown in vitro by Polan et al (1964). Feeding oils increased hydrogenation of 18:3n-3 compared with the control.…”
Section: Resultsmentioning
confidence: 91%
“…Certainly, any unabsorbed unsaturated fatty acids reaching the colon will be exposed to a population of anaerobic bacteria which produce hydrogen and create a reducing environment. It is well known that PUFA are subject to reduction to more saturated homologues by anaerobic bacteria in the rumen (Polan et al 1964), and similar effects have been observed with bacteria isolated from rat intestine (Eyssen and Parmentier 1974). The aim of this study was to investigate whether essential PUFA are biohydrogenated by human colonic bacteria.…”
Section: Introductionmentioning
confidence: 78%
“…‡ Includes cis,cis,trans and cis,trans,trans. -------------------------------------------------- −1 ) -------------------------------------------------- ------------------------------------------------- anaerobic bacteria of the rumen in cattle and sheep has been extensively studied (Polan et al 1964), and similar activities in the rat large intestine were reported by Eyssen and Parmentier (1974). In a study of rumen bacteria by Fujimoto et al (1993), Butyrivibrio fibrisolvens was identified as having the greatest hydrogenating capacity.…”
Section: ------------------------------------------------------No Addmentioning
confidence: 99%
“…Biohydrogenation of unsaturated fatty acids is thought to be mainly because of strains from the Butyrivibrio group in the rumen (Polan et al 1964;van de Vossenberg and Joblin 2003). The Butyrivibrio group, which includes the genus names Butyrivibrio and Pseudobutyrivibrio and a group named Clostridium proteoclasticum (Kopecny et al 2003), comprises strains exhibiting large variation in their 16S rRNA sequences, and the taxonomy of this group of bacteria requires revision (Forster et al 1996;Willems et al 1996;van de Vossenberg and Joblin 2003).…”
Section: Introductionmentioning
confidence: 99%